PENGARUH RASIO PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN - Bima Arya Putra (2014)
This research was conducted to examining influence of profitabilitas ratio and size of company to gift going concern audit report. The samples used were 22 companies listed on the Indonesian Stock Exchanges during 2010-2013. The data used was financial statements audited which has been published in full by Indonesian Stock Exchanges. Variable independent for profitabilitas ratio by using ROA, size of company by using naturalization logarithm and going concern audit report by analyzed auditor opinion. Hypothesis testing was a logistic regression and used SPSS (Statistical Package for Social Science) 20 version for Windows to support and achieve. The results has shown that ratio profitabilitas and size of company changes to going concern audit report has no influence neither simultan nor partial. As result known that nothing influence of profitabilitas ratio and size of company to gift going concern audit report.